Diversity of Xanthomonas citri pv. viticola Populations on Grapevines from Different Locations in India - Bhosale, S.; Saha, S.; Patil, N.; Nazzar, A. (South African Journal of Enology and Viticulture, 2024)
The bacterial leaf spot (BLS) disease caused by Xanthomonas citri pv. viticola (Xcv) is a menace to the production of grapes all over India. The maximum incidence of BLS has been reported in the Maharashtra, Karnataka, and Andhra Pradesh states of India. The symptoms are characterised by water-soaked, angular spots which later become necrotic on leaves. The present study was conducted to investigate the variability of 23 Xcv strains isolated from infected samples collected from Maharashtra, Karnataka, and Tamil Nadu in India. Samples were collected on the basis of the characteristic symptoms. The diversity of all the isolates was assessed phenotypically and genetically. Phenotypic characters included the morphology of colonies, pathogenicity, hypersensitivity, and biochemical tests. Genetic characterisation was assessed using 16S rRNA sequencing. The results exhibited diversity with respect to various phenotypic aspects, like colony size, colour and opacity, the methyl red reduction test, enzyme production, pathogenicity, and a hypersensitivity reaction. The 16S rRNA sequencing showed a distribution of pathogens into two main clusters, which were further divided into nine sub-clusters. The salient findings on Xcv diversity in India will be useful to identify and characterise resistant germplasms against the disease. The nonuniform variability obtained among the isolates suggests that geographical location, climatic factors and the varieties were the driving forces for the evolution of the phytopathogens.